Características de conteúdos de Física das Radiações em três páginas institucionais no Facebook - Moro, Leandro Silva (2020)
For many people, following Facebook pages may seem like an expression of fashion, power and supposed innovation. This investigation consists of attempts to attribute meanings to radiation physics content on three institutional pages on that platform, from its followers. They are: Nuclear Information Center (CIN), Institute of Radioprotection and Dosimetry (IRD) and National Council of Technicians and Technologists in Radiology (CONTER). The objective was to identify characteristics of these contents via these Facebook pages. The methodological strategies adopted were Netnography associated with the Theory of Dialogical Discourse Analysis (ADD) from the Bakhtinian perspective and the Actor-Network Theory (ANT). For the collection and management of data, Ncapture and Nvivo 12 Plus software were added. It was noticed that the content posted on these pages is characterized by the intertwining of followers; themes, topics and subtopics; dimensions (technoscientific, pedagogical, communicational, technological and organizational) and interactions (reactive and mutual). If identifying characteristics of content on these pages is a way of engaging, engendering networks and assigning meanings, the desired innovation, due to its tense nature, does not result from any combinations, mediations and affects. But, of processes that consider the cultural differences of the individuals involved and the technologies to include and promote transformations with educational value, that is, that lead them to reflect on: “what”, “how” and “why” is disseminated and learn; ongoing actions and reactions mediated by the platform; content as part of the culture. Therefore, both institutional pages and Facebook are coupled systems in which followers and content help to create or recreate and prosper. In this opportunity, the type of engagement of followers is a catalyst for experiences and influences some formulate or reformulate of knowledge in the field of radiation physics. If the dominant sense for the platform is the consumption of information, it is up to the followers the necessary and challenging task of learning to consume, which implies thinking about transposing the instructional level and arousing interest in scientific research considering the hypothesis of how it does or can make a difference in their lives.